La vida como un viaje: viaje y peregrinación en la composición pictórica de las Cantigas de Santa María de Alfonso X el Sabio - Chico, M.ª Victoria (Revista de Filología Románica, 2006)
Didactism is one of the major goals in any project promoted by Alphonse X the Wise’s scriptorium. Therefore, it is also one of the main characteristics in the so called Codeices of the Stories’ miniature of the Canticles of Saint Mary, done in the last years of the king’s life, at the end of the XIIIth century. For that purpose, the protagonists’ itineracy in all the miracles is a way used by the painters to produce the feeling of a constant travelling through the illuminated pages. It shows the importance of pilgrimage in Europe at that time.